Preparation and optical properties of highly transparent MgAl1.9Ga0.1O4 ceramics via aqueous gel-casting method. Issue 10 (August 2023) - Yang, Jiuyan; Wang, Hao; Tu, Bingtian; Wang, Bin; Xu, Pengyu; Chen, Qiangguo; Chen, Bowen; Wang, Weimin; Fu, Zhengyi
Abstract: The aqueous gel-casting technology has been widely used to prepare high-quality green body for various transparent ceramics with large dimension and complex shape. However, owing to the severe hydrolysis of MgAl2 O4 powder, it is challenging to obtain thick aqueous slurry with high homogeneity and flowability. In this paper, the surface chemical state of MgAl2 O4 powder was modified by introducing Ga 3+, and stable MgAl1.9 Ga0.1 O4 aqueous slurry with high solid-phase loading (52 vol. %) and low viscosity (136 mPa·s, at a shear rate of 50 s -1 ) was successfully prepared. After pressureless presintering and hot isostatic pressing, the gel-cast sample exhibited much higher optical transmittance and more homogeneous microstructure than the dry-pressed sample, which is mainly derived from the improved homogeneity and densification of the green bodies and ceramics. The optical band gap, infrared cutoff wavelength, static refractive index and dispersion of both MgAl1.9 Ga0.1 O4 and MgAl2 O4 transparent ceramics were systematically compared. It is indicated that the transparent MgAl1.9 Ga0.1 O4 ceramic has the increscent static refractive index of 1.695, the decrescent direct band gap energy of 6.15 eV and absorption coefficient of 0.49 cm -1 at 5 µm, which could be ascribable to the fact that Ga 3+ has different electronic structure, higher electronic polarizability and larger ionic radius in comparison with Al 3+ . This work provides a dependable solution for preparation of spinel oxide ceramics with superior optical properties and large dimension. Highlights: Highly transparent MgAl1.9 Ga0.1 O4 ceramics were prepared by aqueous gel-casting technique and two-step sintering process. Compared with dry pressing, aqueous gel-casting facilitates the preparation of transparent ceramics with large dimension. The infrared cutoff wavelength is broadened(∼0.3 µm) of transparent ceramics since the introduced of Ga.